Experimental and FE analysis for the buckling behavior of hat-stiffened panels under edge compressive loading - Kumar S.; Kumar R.; Mandal S. (My University, 2025)
In this paper, experimental studies on two laminated composite hat-stiffened panels with equally spaced stiffeners have been carried out with application of axial compression load on the panel for the determination of the pre-buckling and post buckling behavior. A non-linear buckling analysis on the hat-stiffened panel has also been performed under compression load with application of finite element tool ABAQUS. From strain analysis at different locations, the local buckling of skin has been observed before the buckling of the panel, and a visual damage has been found near the skin-stiffener and debonding skin-stiffener of the panel during failure of the hat-stiffened panel. The compression load-axial displacement curve of the experiments has correlated well with simulated finite element model result for determination of the buckling behavior of the panel up to the failure load. The out of plane displacement pattern shows that the compressive failure initiated at the edges of the panel and gone to skin-stiffener bonding, and finally failure of the panel occurred due to debonding between skin-stiffener. © 2020, Indian Academy of Sciences.